2007
DOI: 10.1111/j.1469-7580.2007.00779.x
|View full text |Cite
|
Sign up to set email alerts
|

The underside of the cerebral cortex: layer V/VI spiny inverted neurons

Abstract: This paper presents an account of past and current research on spiny inverted neurons -alternatively also known as 'inverted pyramidal neurons' -in rats, rabbits and cats. In our laboratory, we have studied these cells with a battery of techniques suited for light and electron microscopy, including Nissl staining, Golgi impregnation, dye intracellular filling and axon retrograde track-tracing. Our results show that spiny inverted neurons make up less than 8.5 and 5.5% of all cortical neurons in the primary and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 55 publications
(148 reference statements)
3
41
0
Order By: Relevance
“…This band of retrogradely labelled cells extends for millimetres in the secondary visual cortex from the sites of injection of retrograde tracer in the primary visual cortex. This band is particularly cell-populated in brains after multiple injections of tracer; with single injections, labelled cells lie scattered for millimetres in the border between layer 5 and layer 6 [27,28]. These findings have shown that there is a highly convergent yet diffuse projection from the layer 5/6-border principal cells of secondary visual cortex to discrete points of the primary visual cortex.…”
Section: Principal Cells Of Intratelencephalic Projection (Inclusive mentioning
confidence: 77%
See 4 more Smart Citations
“…This band of retrogradely labelled cells extends for millimetres in the secondary visual cortex from the sites of injection of retrograde tracer in the primary visual cortex. This band is particularly cell-populated in brains after multiple injections of tracer; with single injections, labelled cells lie scattered for millimetres in the border between layer 5 and layer 6 [27,28]. These findings have shown that there is a highly convergent yet diffuse projection from the layer 5/6-border principal cells of secondary visual cortex to discrete points of the primary visual cortex.…”
Section: Principal Cells Of Intratelencephalic Projection (Inclusive mentioning
confidence: 77%
“…This cortico-thalamic projection is originated in pyramidal cells but not in spiny inverted or other polymorphic cells of layer 6 (Table 1) [23,28]. This projection is…”
Section: Principal Cells Of Extratelencephalic Projection Sited In Lamentioning
confidence: 99%
See 3 more Smart Citations